2022
DOI: 10.3389/fnbot.2022.1067729
|View full text |Cite
|
Sign up to set email alerts
|

Dance emotion recognition based on linear predictive Meir frequency cepstrum coefficient and bidirectional long short-term memory from robot environment

Abstract: Dance emotion recognition is an important research direction of automatic speech recognition, especially in the robot environment. It is an important research content of dance emotion recognition to extract the features that best represent speech emotion and to construct an acoustic model with strong robustness and generalization. The dance emotion data set is small in size and high in dimension. The traditional recurrent neural network (RNN) has the problem of long-range dependence disappearance, and due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…This study investigated the use of different cepstral coefficient-based features, such as MFCCs, linear predictive cepstral coefficients (LPCCs), and perceptual linear predictive cepstral coefficients (PLPCCs), for emotion recognition in speech. The authors of [ 22 ] suggested a new approach to address the issue of long-term dependence vanishing in RNNs. Specifically, they introduced a novel method using linear predictive Meir frequency cepstrum coefficients and bidirectional LSTM to recognize dance emotions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study investigated the use of different cepstral coefficient-based features, such as MFCCs, linear predictive cepstral coefficients (LPCCs), and perceptual linear predictive cepstral coefficients (PLPCCs), for emotion recognition in speech. The authors of [ 22 ] suggested a new approach to address the issue of long-term dependence vanishing in RNNs. Specifically, they introduced a novel method using linear predictive Meir frequency cepstrum coefficients and bidirectional LSTM to recognize dance emotions.…”
Section: Literature Reviewmentioning
confidence: 99%